2014
DOI: 10.1177/0095244314526746
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of siloxane-based polyurethane elastomers using hexamethylene diisocyanate

Abstract: The present research work was performed to study the properties of siloxane-based polyurethane (SPU) elastomers using aliphatic diisocyanate. SPU samples constituting of hexamethylene diisocyanate, hydroxyl-terminated polybutadiene, and polydimethylsiloxane (PDMS) were synthesized by two-step polymerization technique. Molecular engineering and surface characterization were carried out, and the outcome of the results was discussed. The conventional spectroscopic characterization of the synthesized samples using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Other bonds in the chemical structure of the synthesized polyurethanes are shown in Table 1 . Our results are in agreement with those previously reported by Bai et al ( 2008 ; Zia et al 2014 ).
Fig.
…”
Section: Resultssupporting
confidence: 94%
“…Other bonds in the chemical structure of the synthesized polyurethanes are shown in Table 1 . Our results are in agreement with those previously reported by Bai et al ( 2008 ; Zia et al 2014 ).
Fig.
…”
Section: Resultssupporting
confidence: 94%
“…FTIR spectrum of PDMS has been presented in Figure 2(d) and detailed peak assignment has been presented in our previous study. 22 Some upward peaks can be observed in the spectrum of PDMS and these peaks can be further observed in the spectrum of final PUEs just after the introduction of PDMS with some broadening of peaks because of the change of the environment that strongly support the incorporation of the PDMS in the final material.…”
Section: Resultsmentioning
confidence: 95%
“…The observed peaks in the FTIR spectrum of HTPB (Figure 2(b)) has been comprehensively discussed elsewhere. 22 By the reaction of TDI and HTPB, isocyanate-terminated PU prepolymer was obtained, and the FTIR spectrum of NCO-terminated PU prepolymer has also been presented in Figure 2(c). It is clearly observed that the signal for the OH groups are not present and that of the intensity of NCO groups has reduced to some extent resulting that isocyanate group has been entirely reacted and a signal for NH units appeared at 3323.6 cm −1 suggesting that PU prepolymer had been formed (Figure 2(c)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the wavenumber of 1250 cm −1 , the “spike” in pristine PU can be related to the stretching mode of C‐N structures combined with the stretching mode of N─H structures 84 and the ─CH 2 vibrations 85 . Besides, that disturbance also can relate to the castor oil polyol used in the foam's synthesis, as seen by Alaa et al 87 …”
Section: Resultsmentioning
confidence: 95%